Athermal behavior of core-shell particles in nanocrystalline Cu-Ta. (November 2020) - Marvel, C.J.; Hornbuckle, B.C.; Smeltzer, J.A.; Darling, K.A.; Harmer, M.P.
Abstract: Nanocrystalline Cu-Ta is among the most successfully developed nanostructured alloys involving microstructural design, synthesis, characterization, and testing. However, the interplay of direct and indirect thermal stability mechanisms is still unclear. In this work, mechanically alloyed Cu-10at.%Ta was characterized with atomic-resolution electron microscopy to identify thermal stability mechanisms. A new mechanism involving athermal core-shell particles that were coarsening resistant was discovered after annealing between 100–800 °C up to 1000 h. Evidence suggests that oxide amorphous shells decreased the phase boundary energy thereby reducing the thermodynamic driving force for particle growth and indirectly maximizing thermal stability of Cu(Ta) grains. Graphical abstract: Image, graphical abstract